Literasi Keuangan dalam Pengelolaan Keuangan Pribadi pada Generasi Z - Virna Museliza; Identiti Identiti; Rimet Rimet; Endrianto Ustha (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2023)
Financial Literacy is a series of processes or activities to improve consumers' and communities' knowledge, confidence, and skills to manage their finances better. For twelfth graders who will soon become university students, financial literacy is needed, especially when they will continue their education in a city different from where they live with their parents and family. Therefore, this service was held for students at the State University Entrance Test Guidance, Integrated Guidance 8, at Jl. Sultan Syarif Kasim No.151-153, Pekanbaru. Personal financial management is in the realm of 1) using funds, 2) determining sources of funds, 3) risk management, and 4) future planning. These four things are very relevant to students in Terpadu 8 Guidance who, on average, continue their education outside Pekanbaru. Because the participants of this community service are students who are still dependent on their parents, the use of money that can be avoided is the main emphasis. Everything is so that the funds obtained from parents can be used as well as possible and as economically as possible, and only use funds for good things. Included in good things is setting aside funds every month for charity